Mutations and polymorphisms in TP53 gene--an overview on the role in colorectal cancer - Naccarati, A; Polakova, V; Pardini, B; Vodickova, L; Hemminki, K; Kumar, R; Vodicka, P (Mutagenesis, 2012)
A functionally normal TP53 is essential to protect organisms from developing cancer. Somatic mutations in the gene represent one of the highest recurring perturbations in human tumours, including colorectal cancer (CRC). However, the variegated phenotype of wide spectrum of somatic mutations in TP53 and the complexity of the disease prevent a straight interpretation of the mutational analysis in tumours. In addition to the presence of somatic mutations, polymorphic features of the gene may also contribute to alteration of the normal TP53 functioning and variants, mainly in the form of single nucleotide polymorphisms, can be expected to impact susceptibility to sporadic CRC. In the present study, we reviewed the potential role of alterations in the TP53 gene, both somatic mutations and inherited sequence variations, in predisposition to CRC and in the prognosis and response to therapy. The available data from association studies have mostly shown contradictory outcomes. The majority of the studies were based on limited sample sizes and focussed on a limited number of polymorphisms, with main being the rs1042522 (Arg72Pro). Thus far, there is no possible generalisation of the role of TP53 as also a predictor of therapeutic response and prognosis. The effects of TP53, and its abnormalities, on the response of tumours to cytotoxic drugs, radiation and chemoradiation are complex. However, from studies it is emerging that the inherited genetics of TP53 pathway components could be utilised to further define patient populations in their abilities to induce p53 activity in response to either DNA damaging or p53-targeted therapies.
Keywords: mutace; prognóza; Colorectal Neoplasms; Prognosis; Tumor Suppressor Protein p53; kolorektální nádory; lidé; nádorový supresorový protein p53; Polymorphism, Genetic; Mutation; genetická predispozice k nemoci; polymorfismus genetický; Genetic Predisposition to Disease; Humans